PESANTREN, KYAI DAN TAREKAT DALAM TRANFORMASI SOSIAL - Muhammad Fauzi (Universitas Islam Negeri Imam Bonjol Padang, 2015)
Pesantren has a long history associated with its functions as a forum to educate satri in religious sciences. The central figure is a boarding school clerics who became leader of the school and have the authority which determines the dynamics of intellectual santrinya, even the surroundings.Lately there is a tendency to expand the functions of pesantren not only as a religious institution, but also as a social institution. Consequently, the task is not only working on matters of religion, but also menangggapi social problems. Social work initially may be a side job or a